XbaI polymorphism in the APOB gene and its association with increased cholesterol in children and adolescents: Ouro Preto study - Thomás Viana de Souza; Aline Priscila Batista; Luiz Antônio Alves de Menezes-Júnior; Anna Carolina Motta Costa; Cibelle Ferreira Louzada; Luciano Garcia Lourenção; Wandeir Wagner de Oliveira; Matheus Costa Lima; Maisa Aparecida Marques Araujo; Izabela Vieira Duarte Baptista; Ana Carolina de Souza Soares; Raquel Laranjeira Guedes; et al. (Scientific Reports)
Abstract Atherosclerotic vascular changes can begin during childhood, providing risk for cardiovascular disease (CVD) in adulthood. Identifiable risk factors such as dyslipidemia accelerate this process for some children. The apolipoprotein B (APOB) gene could help explain the inter-individual variability in lipid levels among young individuals and identify groups that require greater attention to prevent CVD. A cross-sectional study was conducted with school-aged children and adolescents in Ouro Preto, Minas Gerais. The study evaluated cardiovascular risk factors’ variables and XbaI polymorphism in the APOB gene for associations with increased total cholesterol (TC). The prevalence of increased TC was notably high, reaching 68.9% in the study population. Carriers of the variant T allele were 1.45 times more likely to develop increased TC in a dominant model (1.09–1.94, p = 0.011). After adjustments, excess weight and a family history of dyslipidemia interacted significantly with XbaI polymorphism in increased TC, resulting in Odds Ratio of 1.74 (1.11–2.71, p = 0.015) and 2.04 (1.14–3.67, p = 0.016), respectively. The results suggest that XbaI polymorphism in the APOB gene may affect the lipid profile of Brazilian children and adolescents and could contribute to the CVD in adulthood.